Envisioning the Ecological Future: Three Perspectives off the Beaten Track - Arnsperger, Christian; Soltysik Monnet, Agnieszka (Text Matters: A Journal of Literature, Theory and Culture, 2023)
With few truly hopeful visions currently emerging from mainstream academia or from established science concerning humanity’s collective environmental outlook, it might be necessary to go off the beaten track in order to see how we can maintain a sense of hope while realistically preparing for the gradual erosion of the world as we know it, therefore also leaving some psychological and emotional room for a sense of the tragic. This essay considers three lesser-known but, in our eyes, important contemporary perspectives on the ecological future: Ernest Callenbach’s “ecotopia,” John Michael Greer’s “catabolic descent” and William deBuys’s “hospice for Earth”—all three of which aim to challenge the currently still dominant focus on the binary of “progress or apocalypse” that flows from modern thought. We critically examine these visions and argue that, when combined, they offer an approach to the ecological future that is both more realistic and more inspiring. In essence, Callenbach’s ecotopian vision still has significant traction—and an almost “erotic” appeal—today, but needs to be adapted to contemporary ecological realities through Greer’s and deBuys’s insights into decline, grief and the tragic.